Settlement, society and cognition in human evolution : landscapes in the mind - Coward, Fiona Susan; Hosfield, Robert; Pope, Matthew; Wenban-Smith, F. F. (Francis F.) (New York : Cambridge University Press, 2015)
'This volume provides a landscape narrative of early hominin evolution, linking conventional material and geographic aspects of the early archaeological record with wider and more elusive social, cognitive and symbolic landscapes. It seeks to move beyond a limiting notion of early hominin culture and behavior as dictated solely by the environment to present the early hominin world as the outcome of a dynamic dialogue between the physical environment and its perception and habitation by active agents. This international group of contributors presents theoretically informed yet empirically based perspectives on hominin and human landscapes'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Human evolution -- Social aspects; Human settlements -- History -- To 1500.; Cognition and culture -- History -- To 1500.; Material culture -- History -- To 1500.; Prehistoric peoples; Paleolithic period; Social archaeology; Landscape archaeology; Antiquities, Prehistoric